Edukasi Bahaya Mercury (Hg) Pada Masyarakat Pelaku Penambangan Emas Tanpa Izin (Peti) - Halid, Idham; Pauzan (STAI Al-Amin Gersik Kediri Lombok Barat-NTB, 2023)
Mining activities are often the leading cause of declining environmental quality and public health status. This is inseparable from the impact of toxic and hazardous waste materials (B3), one of which is mercury. Mercury is the primary weapon of gold miners in the processing process. The community of Kedaro Village, Sekotong District, has an average community activity as an unlicensed gold miner and, as a whole, uses mercury. Education on the dangers of mercury aims to provide insight to the public about the dangers of mercury to health and the environment so that they have preventive measures to protect their health and the environment. This service is carried out using the method of education/counselling and health problems for the mining community without a permit. This counselling activity is carried out by presenting material, providing education on how to wash hands properly and adequately, and health checks. The results of the physical examination conditions on miners' skin show changes in the colour and shape of the skin. Of the 21 counselling participants, on average, they did not understand the dangers of mercury and the occurrence of a decrease in skin health. This activity was carried out well, but the number of participants could have been more optimal, which demanded the attention of all of us to provide continuous education.